Use of electrical resistance measurement to assess the water saturation profile in porous limestones during capillary imbibition. (20th March 2018) - Hassine, Mohamed Ahmed; Beck, Kévin; Brunetaud, Xavier; Al-Mukhtar, Muzahim
Highlights: Development of a new method for estimation of water content in building stones. Relationship between electrical resistance and degree of saturation in stones. Profile of degree of saturation in porous stones during capillary imbibition. Imbibition curve of stones determined from electrical resistance measurement. Abstract: Electrical resistance can be a relevant indicator for the assessment of water transfer in porous materials. The aim of this work was to establish a relationship between electrical resistance and water saturation in the case of two limestones used as building stones in the Château de Chambord in France: tuffeau and Richemont stone. For this purpose, firstly the electrical resistance matching different values of degree of saturation was investigated. Experimental measurements were performed to determine a relationship between the electrical resistance and the degree of water saturation, with high sensitivity. Secondly, using this relationship, the capillary imbibition curves and imbibition coefficients of the two stones were precisely determined by electrical resistance measurement.